Building The Concept Of Strengthening Middle Managers Through Managerial Skills Program ( Strengthening The Organization Through Strengthening Middle Management ) - Wahyu Wismanto Hadi; Iim Wasliman; IdaTejawiani; Faiz Karim Fatkhullah (CV. Inara, 2022)
Strategy Human Resource development at the level of middle management important companies in the era disrupsi this. The development of human resources in the middle-management level is performed to form a personal quality skills, ability to work, and loyalty in the company. Strategy human resource development at the level of middle management can be done with many ways to develop it. Some of the strategies that can be learned by companies in developing and find the human resources in the middle-management level needed one of them through a training program that is hardwired. Training is carried out by developing individual in the form of increased skills, knowledge and attitude. Training is not only useful for employees, but also the company. In order to improve managerial ability, especially on the line of middle management in the company in need of improvement and continuous human resource development in order to create synergy and teamwork company. That the development and competition of the current human resources to be a major factor in the success in winning the competition. The ability and capacity of middle management will be different from one company to another. The critical point of the growth of the company existing on the capacity and capability of middle management.Thus, the need training programs applicable and integrated for the development of human resources in the middle-management level that exists as one of the main assets to a company that everlasting growth. This Program must be supported by all parties corporate executives for the achievement of the vision, mission and goals of the organization. Human resource development at the level of middle management is done through training to improve the ability of the performance of the personal there. The form of the development of human resources in the middle-management level can be done in formal or non-formal for their careers. Every human resources at the level of middle management need training to overcome various problems in their work by teaching steps and the right way.